Pengembangan Sistem Informasi Registrasi Pelayanan Administrasi Terpadu Kecamatan (Paten) Di Kecamatan Tarogong Kidul Kabupaten Garut - Reza Ardiansyah; Efi Sofiah (Jurnal Wawasan Ilmiah, 2019)
This research aims to make learning model accounting with accounting application program so that learning becomes easier accounting, challenging and fun for students and teachers of accounting so difficult to study accounting assumption can be helped with accounting application program that the author designed. The problem often faced by students in learning accounting including; transaction that is pretty much it often wrong in the calculation of the transaction, despite being put on mechanical calculators (calculator), recording repeated in subsequent keform posting one transaction that requires a long processing time, the difficulty in preparing the financial statements (Income Statement, Balance Sheet, Capital statement, and Retained Earnings) because students have to memorize any accounts that must exist on the financial statement, it causes less mandirinya in learning more centralized accounting finally learning to teachers. With a program he designed accounting application with Delphi programming language, learning problems occurred in accounting can be helped, because the author designed programs available facilities such as teaching materials, a data input form (General Journal) where the program automatically adds the transaction is entered, with only one input data, then the data is directly accessible to the next form as the form of the accounting equation, the form of financial statements (Balance sheet, Income Statement, statement of Capital and Retained Earnings), as well as for the ledger and work sheets (annual report). So that the processing time to be effective and efficient as well as students become productive. Accounting application program design will be tested on students making an accounting class 1 semester of the 2014/2015 academic year at the Department of informatics management with accounting reasons as writers first in the majors in order to make it easier to analyze the reliability and ease of application programs accounting in analyzing the program on learning process accounting. From the results of this study are expected to be useful for accounting faculty, students, high school, vocational school, so tertananm independent learning, challenge and fun, the general public who want to study accounting easily and for science as a reference model of the development of the application of ICT in learning. Keywords: Analysis, Information Systems, Accounting Education, ICT, Program Application.